The kotwali thana central cooperative association (KTCCA): a study on sustainability of two-tier cooperative system - Alam, Md. Mahbub-ul (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2006.